Sub-Coronal Inflatable Penile Prosthesis Placement with Modified No-Touch Technique: A Step-by-Step Approach with Outcomes. Issue 2 (1st February 2016) - Weinberg, Aaron C.; Pagano, Matthew J.; Deibert, Christopher M.; Valenzuela, Robert J.
ABSTRACT: Introduction: The surgical treatment of disorders of male sexual function requires specific exposure to correct the underlying problem safely and efficiently. Currently, sub-coronal exposure is used for treatment of phimosis, Peyronie's disease plaque (PDP), and semirigid penile prosthesis insertion. Infra-pubic and scrotal incisions are used for inflatable penile prosthesis (IPP) placement. However, men who present with several disorders might require multiple procedures and surgical incisions. Aim: To report a prospective review of our surgical experience and outcomes with a single sub-coronal incision for IPP placement with a modified no-touch technique. This approach allows for access to the entire corporal body for multiple reconstructive procedures. Methods: Two hundred men had IPPs placed through a sub-coronal incision using our modified no-touch technique. The penis was degloved to the level of the penoscrotal junction and the dartos muscle was everted and secured to the drapes. This allowed exclusion of the scrotal and penile skin from the operative field. After artificial erection, the patient's corpora were inspected for PDP and other abnormalities. Penoscrotal IPP models were placed in all cases with insertion proximal to the penoscrotal junction. After placement of the IPP, the abnormalities were repaired. Main Outcome Measures: Feasibility of the procedure, operative times, complication rate, utilization of accessory, reconstructive procedures, and post-operative penile length. Results: Of the 200 men who had IPP placement, 92 had PDP that was treated, 106 (53%) consented to circumcision, 24 (12%) had their reservoir placed ectopically, and 31 (16%) had a prosthesis exchanged through the sub-coronal technique. Mean operative time was 73 minutes (39–161 minutes). Conclusion: Specialists in the surgical treatment of disorders of male sexual function can perform multiple procedures safely and easily through a modified no-touch single sub-coronal incision. This approach allows access to the entire corporal body, providing excellent visibility and allowing the surgeon to perform multiple penile reconstructive surgeries through a single incision.